(untitled) (Research, Society and Development, 2025)
This study aimed to analyze the epidemiological profile of hospital admissions for surgical treatment of hydrocele in Northeastern Brazil from 2015 to 2024. This is a quantitative, descriptive, cross-sectional investigation based on secondary data from the Brazilian Unified Health System’s Hospital Information System (SIH/SUS). A total of 29,690 hospitalizations were identified, with a total cost exceeding R 9 million and 44,456 hospital days. The Northeast was the second region with the highest number of procedures, behind only the Southeast. A decline in surgeries was observed in 2020, followed by a recovery through 2024, possibly related to the COVID-19 pandemic. Despite the low mortality rate, the underreporting of deaths stands out as a major limitation. The findings offer relevant insights for public health planning and for strengthening regional surgical care within the SUS.